PENGARUH PENERAPAN LEMBAR KEGIATAN SISWA (LKS) BERBASIS KONTEKSTUAL TERHADAP HASIL BELAJAR DAN AKTIVITAS SISWA PADA MATERI PLANTAE KELAS X DI SMA N 6 METRO - Wening Galih Paramita; Widya Sartika Sulistiani; Triana Asih (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
The contextual based student worksheet (LKS) application aims to allow students to be active in learning, such as observing, solicit, collecting information or experimentation, associating or processing information and communicating. The contextual based student worksheets (LKS) make students easier to understand the material being studied, and the attractive LKS and various herbs presented can make students more active and less bored in the learning process. The purpose of this research is to determine the influence of implementation of student activity sheets (LKS) based on contextual learning outcomes and student activity in the class X SMA Negeri 6 Metro. This type of research is a pseudo experiment (Quasy Experiment). Research site of SMA Negeri 6 Metro. The population in this study was all grade X students with a total of 78 students consisting of 3 classes. The samples used in this study were two classes of X MIPA 2 and X MIPA 3. X MIPA 2 is an experimental class consisting of 26 students. Whereas X MIPA 3 becomes the control class. The study was held on 28 January-13 February 2020. The test of the structure in this study uses a test of normality and homogeneity. Hypothesis test using T test. Based on the results of the hypothesis testing obtained that, the two average similarity test was obtained t_hit (9.12) > t_daf (2.02) and the test of the two average difference obtained t_hit (9.12) > t_daf (1.68). The test results of two average similarities prove that there is an average difference in learning outcomes in experimental classes and control classes. The test results of two average differences proved that the average learning outcome in the level of the ecperimen was higher than in the control class. The contextual based student activity sheet (LKS) application affects learning outcomes and student activity on the Plantae material for the X-grade SMA Negeri 6 Metro students